2007
DOI: 10.1038/ismej.2007.4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial ecology meets electrochemistry: electricity-driven and driving communities

Abstract: Bio-electrochemical systems (BESs) have recently emerged as an exciting technology. In a BES, bacteria interact with electrodes using electrons, which are either removed or supplied through an electrical circuit. The most-described type of BES is microbial fuel cells (MFCs), in which useful power is generated from electron donors as, for example, present in wastewater. This form of charge transport, known as extracellular electron transfer, was previously extensively described with respect to metals such as ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
283
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(288 citation statements)
references
References 57 publications
3
283
0
2
Order By: Relevance
“…Previous studies of MFCs inoculated with Firmicutes isolates only produced current in the presence of an exogenous electron shuttle (Rabaey et al, 2005(Rabaey et al, , 2007Milliken and May, 2007;Pham et al, 2008) or as a byproduct of glucose fermentation (Park, 2001;Kim et al, 2005). Therefore, it was recently concluded that the presence of Gram-positive bacteria in an MFC is an outcome of ecological interaction with Gram-negative electricity-producing organisms rather than a functional interaction and electron transfer with the electrode surface (Rabaey et al, 2007).…”
Section: Thermophilic Microbial Fuel Cells Kc Wrighton Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of MFCs inoculated with Firmicutes isolates only produced current in the presence of an exogenous electron shuttle (Rabaey et al, 2005(Rabaey et al, , 2007Milliken and May, 2007;Pham et al, 2008) or as a byproduct of glucose fermentation (Park, 2001;Kim et al, 2005). Therefore, it was recently concluded that the presence of Gram-positive bacteria in an MFC is an outcome of ecological interaction with Gram-negative electricity-producing organisms rather than a functional interaction and electron transfer with the electrode surface (Rabaey et al, 2007).…”
Section: Thermophilic Microbial Fuel Cells Kc Wrighton Et Almentioning
confidence: 99%
“…Although 16S rDNA sequences belonging to the Firmicutes have previously been detected in the anode communities of active fuel cells (Lee et al, 2003;Kim et al, 2004Kim et al, , 2006Rabaey et al, 2004Rabaey et al, , 2007Aelterman et al, 2006;Hamid Rismani-Yazdi et al, 2007;Mathis et al, 2007), there are a limited number of publications where Firmicutes represent a dominant portion (450%) of the anode community composition (Rabaey et al, 2004(Rabaey et al, , 2007Aelterman et al, 2006;Hamid Rismani-Yazdi et al, 2007;Mathis et al, 2007). Previous studies of MFCs inoculated with Firmicutes isolates only produced current in the presence of an exogenous electron shuttle (Rabaey et al, 2005(Rabaey et al, , 2007Milliken and May, 2007;Pham et al, 2008) or as a byproduct of glucose fermentation (Park, 2001;Kim et al, 2005). Therefore, it was recently concluded that the presence of Gram-positive bacteria in an MFC is an outcome of ecological interaction with Gram-negative electricity-producing organisms rather than a functional interaction and electron transfer with the electrode surface (Rabaey et al, 2007).…”
Section: Thermophilic Microbial Fuel Cells Kc Wrighton Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…A potential limitation on the metabolism for cells closer to the anode surface is lack of electron donor or nutrients due to cells in the outer section consuming these components (He et al, 2005;Marcus et al, 2007;Rabaey et al, 2007;Torres et al, 2008). G. sulfurreducens genes encoding acetate transporters that are more highly expressed when acetate is limiting have been identified (Risso et al, 2008).…”
Section: Transcriptional Analysis Of Outer Versus Inner Members Of Cumentioning
confidence: 99%
“…Arguably, mediator dependent electron transfer is the most common mode of electron transfer, where a wide range of bacteria accomplish extracellular electron transfer (EET) by producing various soluble electron shuttles or mediators (Rabaey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%